Effects of Season on Abundance and Diversity of Soil Arthropods in Mangli Coffee Plantation Kediri Regency, East Java, Indonesia - Suheriyanto, Dwi; ., Soemarno; Yanuwiadi, Bagyo; Setyo Leksono, Amin; Heru Prasetiyo, Dony; Rizal Permana, Syaiful (International Journal of Engineering and Technology, 2019)
The soil arthropod diversity is influenced by the season rather than the plantation age. Arthropods will respond to every aberration from normal environmental conditions, against high or low temperature thresholds to respond in many ways.  The study was carried out in Mangli coffee plantation Kediri regency to determine the effect of season on the abundance and diversity of soil arthropods.  In each season is an installed systematically 30 pitfall traps. The environmental factors as measured where the temperature and humidity of soil, soil organic carbon, soil organic matter, N, P and K. The soil arthropods  abundance was analyzed using PCA. The soil arthropod diversity was analyzed using Shannon index, dominance and equitability. The environmental factor effect on the soil arthropod abundance was analyzed using CCA. The season is very effect on the soil arthropod abundance in Mangli coffee plantation. The Myrmica genus is very abundant in the dry season while in rainy season is Entomobrya genus. Based on PCA result, the dry season is characterized by Ponera genus while the rainy season is characterized by  Entomobrya and Neoponera genus. The soil arthropod diversity in rainy season is higher than the dry season. The taxa number, individual number, Shannon diversity index and equitability in the rainy season are higher than the dry season. The most of environmental factors of Mangli coffee plantation in dry season except temperature and phosphor are higher than rainy season. Based on CCA can be known that temperature and phosphor influence the distribution of most soil arthropods in rainy season.